Resource Management and Backhaul Routing in Millimeter-Wave IAB Networks Using Deep Reinforcement Learning - Maharaj, Sunil (University of Pretoria, 2023)
Thesis (PhD (Electronic Engineering))--University of Pretoria, 2023..